Modeling Chemical Tests and Fiber Identification of Paper Materials Using Principal Component Analysis and Specular Reflection FTIR Data - Julie H. Wertz; Arthur A. McClelland; Debora D. Mayer; Penley Knipe (Heritage, 2022)
Paper materials and works of art on paper such as drawings, watercolors, prints, books, and manuscripts represent a large portion of museum, archive, and library collections. However, paper materials are infrequently the subject of technical studies due to inherent limitations in their analysis such as the fragility of the paper substrate, a lack of suitable sampling opportunities, and the presence of mixed, but chemically similar cellulosic materials. The application of principal component analysis (PCA) modeling to specular reflection FTIR data has the potential to provide a non-invasive means of analysis for major and minor components in paper materials. Using known study collection objects, PCA models distinguishing paper sizing materials and fiber types based on specular reflection FTIR data were successfully demonstrated thus providing a plausible alternative method for the identification of paper materials in collection objects without the need for destructive testing or sampling of the object.